2019
DOI: 10.1038/s41699-019-0088-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of substrate-induced anisotropic growth of monolayer WS2 by kinetic Monte Carlo simulations

Abstract: Controlled anisotropic growth of two-dimensional materials provides an approach for the synthesis of large single crystals and nanoribbons, which are promising for applications as low-dimensional semiconductors and in next-generation optoelectronic devices. In particular, the anisotropic growth of transition metal dichalcogenides induced by the substrate is of great interest due to its operability. To date, however, their substrate-induced anisotropic growth is typically driven by the optimization of experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
(40 reference statements)
3
14
0
Order By: Relevance
“…Under such local spaceconfined environment, we propose that the kinetic growth can be induced combined with vdW substrate effect. Recent kinetic Monte Carlo simulation results have also predicted the substrate-induced anisotropic growth of WS 2 NRs, which further confirms our experimental results [36]. Our methods pave a new route for the control-lable growth of TMDC NRs, which is significant for exploring promising applications based on TMDC NRs.…”
Section: Tmdc Nr Growth Mechanismsupporting
confidence: 87%
“…Under such local spaceconfined environment, we propose that the kinetic growth can be induced combined with vdW substrate effect. Recent kinetic Monte Carlo simulation results have also predicted the substrate-induced anisotropic growth of WS 2 NRs, which further confirms our experimental results [36]. Our methods pave a new route for the control-lable growth of TMDC NRs, which is significant for exploring promising applications based on TMDC NRs.…”
Section: Tmdc Nr Growth Mechanismsupporting
confidence: 87%
“…The comparisons suggest that the anisotropic growth of MoS 2 is most possibly induced by the anisotropic property of substrate: including surface adsorption and surface diffusion, which are considered as two key factors that influence the topological evolution of TMDs and would result in the anisotropy growth. [ 44 ] Actually, the twofold symmetry surface structure of a‐plane sapphire makes it an intrinsic anisotropic substrate. In this regard, the anisotropic substrate induces symmetry breaking of incipient MoS 2 seed and enables rapid crystal growth in one direction owing to the highly asymmetric energy landscape experienced by the MoS 2 crystal.…”
Section: Figurementioning
confidence: 99%
“…At higher temperatures, the migration coefficient is larger and adatoms can diffuse over longer distances before attaching to an island. Recent theoretical calculations showed that the migration energies of W and S atoms on the edge site of WS 2 are about 3.81 eV and 1.02 eV, respectively [ 53 ]. Thus, the lateral growth of WS 2 is mainly limited by W migration with a migration barrier of 3.81 eV.…”
Section: Resultsmentioning
confidence: 99%